EXPLORING PRAGMATIC DEVELOPMENT IN 4-YEAR-OLD CHILDREN: AN INTERACTIONALIST PERSPECTIVE - Salamah, Siti; Zultiyanti, Zultiyanti (English Review: Journal of English Education, 2024)
Many studies of pragmatic acquisition in Indonesia have been carried out, but they are only limited to aspects of speech acts. For this reason, it is necessary to have an in-depth study related to aspects of acquiring pragmatics in children. This research was conducted using a qualitative descriptive method. This study aims to describe the main issues regarding pragmatic acquisition in children aged 4 years. The research data was obtained at ABA Nitikan Yogyakarta Kindergarten. As for the technique of data collection, it was done by observation method with recording and note-taking techniques. Data analysis uses the Miles & Huberman flow model. The validity of the data is achieved by triangulation of methods and theories. Data triangulation was carried out by extracting data from three sources, namely in-depth observations in class, audio recordings of class interactions and reflective analysis of field notes. Theoretical triangulation is carried out by comparing the results of research data acquisition with relevant theoretical perspectives to avoid the researcher's individual bias on the resulting findings or conclusions. The results of a study of the acquisition of pragmatics in children show that 4 years old children in ABA Nitikan Yogyakarta Kindergarten have acquired the aspects of Joint Attention (JA) as much as 4%, Common Ground (CG) 9%, Convention and Contrast (CC) 11%, Feedback and Repair (FR) 9%, and Speech Act (SA) 67%.